The workplace : - Pace, Joe (Joseph) (McGraw-Hill, 2006)
Professional success in the 21st century demands that people work together to achieve their goals. Book Two: Interpersonal Strengths and Leadership, explores and develops the skills that make a person a good teammate and a good leader. This book helps students develop a standard of excellence and pride in work and addresses ethics, trust, respect, strategic thinking, and modeling leadership techniques.